Respostas
respondido por:
1
Sabemos que:
log a + log b = log a.b
log 10 = 1
Logo:
log (x + 2) + log (x - 2) = 1
log (x + 2).(x - 2) = log 10
log (x² - 2x + 2x - 4) = log 10
log (x² - 4) = log 10
Igualando os logaritmandos, teremos que:
x² - 4 = 10
x² = 10 + 4
x² = 14
x = √14
log a + log b = log a.b
log 10 = 1
Logo:
log (x + 2) + log (x - 2) = 1
log (x + 2).(x - 2) = log 10
log (x² - 2x + 2x - 4) = log 10
log (x² - 4) = log 10
Igualando os logaritmandos, teremos que:
x² - 4 = 10
x² = 10 + 4
x² = 14
x = √14
respondido por:
1
Espero ter ajudado.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás